“Vino nuovo in otri nuovi”: alcune prime note circa le sfide del presente per il diritto canonico e la canonistica (Stato, Chiese e pluralismo confessionale, 2024)
“New wine into new wineskins”: some first notes on the current challenges for canon law ABSTRACT: Inspired by the Summary Document of the recent Synod of Bishops, which requests a revision of the Code of Canon Law and the Code of Canons of the Eastern Churches, this study intends to reflect on the contribution that canonical doctrine can offer for this revision. Specifically, the study analyzes the current Code as a result of both the Second Vatican Council and the legal classifications specific to the positivist culture during the 19th and 20th centuries and, consequently, it observes the necessity, from a de iure condendo perspective, to approach the work articulated towards a mature acceptance of certain aspects of the Second Vatican Council not appropriately valued in the drafting of the Code, such as the pneumatological renewal of the theology and ecclesiology of communion. Given these remarks, it is possible to move in the direction indicated by the Synod, avoiding "pouring the new wine of the Synod into old wineskins" of the now outdated juridical categories. In this perspective, the study identifies four potential areas for renewal, both urgent and achievable.SOMMARIO: 1. Premessa - 2. Una pro-vocazione alla canonistica - 3. Un complesso lavoro di ricezione - 4. Alcune questioni sulle quali riflettere - 5. Considerazioni di sintesi.